Sandwich-type PLLA-nanosheets loaded with BMP-2 induce bone regeneration in critical-sized mouse calvarial defects. (1st September 2017) - Huang, Kuo-Chin; Yano, Fumiko; Murahashi, Yasutaka; Takano, Shuta; Kitaura, Yoshiaki; Chang, Song Ho; Soma, Kazuhito; Ueng, Steve W.N.; Tanaka, Sakae; Ishihara, Kazuhiko; Okamura, Yosuke; Moro, Toru; et al.
Graphical abstract: Abstract: To overcome serious clinical problems caused by large bone defects, various approaches to bone regeneration have been researched, including tissue engineering, biomaterials, stem cells and drug screening. Previously, we developed a free-standing biodegradable polymer nanosheet composed of poly(L-lactic acid) (PLLA) using a simple fabrication process consisting of spin-coating and peeling techniques. Here, we loaded recombinant human bone morphogenetic protein-2 (rhBMP-2) between two 60-nm-thick PLLA nanosheets, and investigated these sandwich-type nanosheets in bone regeneration applications. The PLLA nanosheets displayed constant and sustained release of the loaded rhBMP-2 for over 2 months in vitro . Moreover, we implanted the sandwich-type nanosheets with or without rhBMP-2 into critical-sized defects in mouse calvariae. Bone regeneration was evident 4 weeks after implantation, and the size and robustness of the regenerated bone had increased by 8 weeks after implantation in mice implanted with the rhBMP-2-loaded nanosheets, whereas no significant bone formation occurred over a period of 20 weeks in mice implanted with blank nanosheets. The PLLA nanosheets loaded with rhBMP-2 may be useful in bone regenerative medicine; furthermore, the sandwich-type PLLA nanosheet structure may potentially be applied as a potent prolonged sustained-release carrier of other molecules or drugs. Statements of Significance: Here we describe sandwich-type poly(L -lactic acid) (PLLA) nanosheets loaded with recombinant human bone morphogenetic protein-2 (rhBMP-2) as a novel method for bone regeneration. Biodegradable 60-nm-thick PLLA nanosheets display strong adhesion without any adhesive agent. The sandwich-type PLLA nanosheets displayed constant and sustained release of the loaded rhBMP-2 for over 2 months in vitro . The nanosheets with rhBMP-2 markedly enhanced bone regeneration when they were implanted into critical-sized defects in mouse calvariae. In addition to their application for bone regeneration, PLLA nanosheets may be useful for various purposes in combination with various drugs or molecules, because they displays excellent capacity as a sustained-release carrier.